2023
DOI: 10.3389/fonc.2023.1082441
|View full text |Cite
|
Sign up to set email alerts
|

LIM1 contributes to the malignant potential of endometrial cancer

Abstract: IntroductionThe incidence of endometrial cancer (EC) has been increasing worldwide. However, because there are limited chemotherapeutic options for the treatment of EC, the prognosis of advanced-stage EC is poor.MethodsGene expression profile datasets for EC cases registered in The Cancer Genome Atlas (TCGA) was reanalyzed. Highly expressed genes in advanced-stage EC (110 cases) compared with early-stage EC (255 cases) were extracted and Gene Ontology (GO) enrichment analysis was performed. Among the enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…For our study, we analyzed three distinct microarray datasets from the Gene Expression Omnibus (GEO) database hosted by the NCBI. These datasets corresponded to PCOS, endometrial cancer, and ovarian cancer, identified by the accession numbers GSE199225[12], GSE215413[13], and GSE174670[14], respectively. Our selection criteria included considering only complete samples categorized as either cases or controls.…”
Section: Methodsmentioning
confidence: 99%
“…For our study, we analyzed three distinct microarray datasets from the Gene Expression Omnibus (GEO) database hosted by the NCBI. These datasets corresponded to PCOS, endometrial cancer, and ovarian cancer, identified by the accession numbers GSE199225[12], GSE215413[13], and GSE174670[14], respectively. Our selection criteria included considering only complete samples categorized as either cases or controls.…”
Section: Methodsmentioning
confidence: 99%
“…For our study, we analysed three distinct microarray datasets from the GEO database hosted by the NCBI. These datasets corresponded to PCOS, EC and OC, identified by the accession numbers GSE199225,[ 15 ] GSE215413[ 16 ] and GSE174670,[ 17 ] respectively. Our selection criteria included considering only complete samples categorised as either cases or controls.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%